1995
DOI: 10.1002/mar.4220120703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient odors on slot‐machine usage in a las vegas casino

Abstract: Studies have shown that ambient aromas impact on consumers' behavior. To further investigate such effects, for one weekend, two slot-machine areas in a Las Vegas casino were odorized, each with a different aroma. A third slot-machine area served as an unodorized control. The amounts of money gambled in slot machines located in the three areas were measured and compared for the weekend of the odorization and for the weekends before and after as well, to control for extraneous variables. Our data show that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
3
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 1 publication
2
140
3
7
Order By: Relevance
“…In the same study, many of the subjects reported they would pay 10-15% more for the product (Lindstrom and Kotler 2003). In a Las Vegas casino, a pleasant ambient scent in an area of the casino was related to 45% more revenue than comparable non-scented slot machine areas (Hirsh 1995). In another study, a sweet citrus ambient scent nearly doubled the average total purchases in a retail setting, from $55 to $90 per customer.…”
Section: How Scents Are Used In Marketingmentioning
confidence: 91%
“…In the same study, many of the subjects reported they would pay 10-15% more for the product (Lindstrom and Kotler 2003). In a Las Vegas casino, a pleasant ambient scent in an area of the casino was related to 45% more revenue than comparable non-scented slot machine areas (Hirsh 1995). In another study, a sweet citrus ambient scent nearly doubled the average total purchases in a retail setting, from $55 to $90 per customer.…”
Section: How Scents Are Used In Marketingmentioning
confidence: 91%
“…Some articles investigate the impact of scent in terms of products or brands (Bone & Jantrania, 1992;Mitchell, Kahn & Knasko, 1995;Morrin & Ratneshwar, 2000) and some in terms of products and stores (Spangenberg, Crowley & Henderson, 1996;Orth & Bourrain, 2005). Most of the articles focus on the effectiveness of ambient scent in retail store or other store-like environments (Knasko, 1989;Hirsch, 1995;Mattila & Wirtz, 2001; Gueguen & Petr, 2006). Increasingly, publications deal with ambient scent in shopping mall settings (Chebat & Michon, 2003;Michon, Chebat & Turley, 2005).…”
Section: The Effect Of Ambient Scent On Consumers' Perception Emotiomentioning
confidence: 99%
“…In another three studies the whole population was observed over the defined research period (Knasko, 1989;Hirsch, 1995;Gueguen & Petr, 2006). A convenience sampling approach was applied in all the others, such that the results could be affected by sample selection bias and cannot be seen as representative for a wider population.…”
Section: Sample Selection Proceduresmentioning
confidence: 99%
“…Findings on the olfactory stimuli suggest that pleasing aromas make customers spend more time at the shopping areas and make them feel good (Slatten et al, 2011;Bowie and Buttle, 2009;Hulten et al, 2009;Lindstrom, 2007;Shaw, 2007;Hirsch, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%